Content and Language Integrated Learning in primary schools in Andalusia: A qualitative study on teachers’ concerns - Szczesniak, Anna (Círculo de Lingüística Aplicada a la Comunicación, 2024)
Despite the unanimous endorsement of the Content and Language Integrated Learning in mainstream education, the bilingual programme is not free from challenges. Hence, the main objective of the study was to examine the primary school teachers’ perceptions of the dual-focused approach to detect the major limitations and determine if there were potential differences within each cohort of teachers. Data were obtained from a questionnaire sent to all bilingual primary schools in Andalusia (Spain). For the purpose of the present study qualitative data were analysed using the software NVivo. The results of the study revealed that teachers’ needs have not been addressed sufficiently as they expressed deep concern over the scarcity of teacher training schemes, insufficient time for coordination, inappropriate design of the materials, little or no support provided to them and increased workload. Furthermore, with regards to the within-cohort comparisons, content teachers seem to be in greatest need of more assistance and training initiatives. These outcomes merit further attention and should feature on the agenda of educational policymakers as not addressing these issues properly might threaten the viability of the bilingual project.